Caracterização de áreas potencialmente favoráveis para produção de cana-de-açúcar na bacia hidrográfica do Alto Paranapanema envolvendo aspectos climáticos, físicos e ambientais - Ribeiro, Gabriela Vasconcelos (Universidade Federal de São Carlos, 2021)
The characterization of physical and climatic aspects and the diagnosis of land use and land cover of hydrographic basins using geoprocessing tools is extremely important to assist in agro-environmental planning and zoning. Sugarcane, one of the main crops in Brazilian agribusiness, has an expressive distribution in the state of São Paulo, historically concentrating in the north, west and center of the state, but with a tendency to expand to other regions, such as the region south region of São Paulo, in the Alto Paranapanema hydrographic basin (BH-ALPA). This work aimed to characterize climatic (precipitation and temperature), physical and environmental aspects of the Alto Paranapanema hydrographic basin and identify potentially favorable areas for sugarcane production, by using geotechnologies. From SRTM images, we reclassified the slope into 2 classes (from 0 to 15% and above 15%). Furthermore, using images from the MapBiomas 5.0 collection, we mapped the areas with sugarcane for the Years of 1989, 1999, 2009 and 2019 for the whole study area. Regarding the environmental variables, we carried out a diagnosis of the permanent preservation areas (APP) of the main watercourses. With CBERS 4A images, it was possible to reclassify the land use and land cover into suitable and unsuitable areas for sugarcane production. For the climatic suitability of the basin, we used the data from the agro-environmental zoning of the São Paulo State Environment’s Office. We further used daily data of temperature and precipitation of 11 meteorological stations of INMET, to create climatic charts showing its spatial distribution by using the interpolation method, covering a time span of 10 years. The highest temperature values occur in the northwestern region of the basin, while the lowest occur in the southern and southeastern regions. Precipitation was higher values in the north/northwest region during summer, whereas in the winter, precipitation was overall higher in the south/southeast. According to other works, we observed that about 72% of the APPs are irregular and need to be recovered. That said, the basin still has about 33% of its area classified as suitable áreas for sugarcane production, while 67% correspond to non-suitable areas.
Characterization of potentially favorable areas for sugarcane in the Alto Paranapanema basin involving climatic, physical and environmental aspects
Keywords: Cana-de-açúcar; Aptidão climática; Geoprocessamento; OUTROS::CIENCIAS; OUTROS